An Assortment of Synthesis Methods of Silver Nanoparticles: A Review - Jayaprakash, N.; Suresh, R.; Rajalakshmi, S.; Raja, S.; Sundaravadivel, E. (Asian Journal of Chemistry, 2019)
Silver nanoparticles (AgNPs) have received much attention in the recent decades due to their peculiar physical, chemical and biological properties. These properties made AgNPs as potential material in several fields. Silver nanoparticles have been exploited to the great extent, since it is being used as "colloidal silver" from the last century. This paper involves significantly reviewing the AgNPs from the perception of research trends such as number of publications in year wise, article types, publication title, country wise publication, patented filed and also different synthesis methods. Normally, nanoparticles are synthesized by top-to-bottom method and bottom-to-top method, which include physical, chemical, and biological/green methods. These methods are having numerous advantages and disadvantages. In this review, perspectives of research trends and various synthesis methods of AgNPs have been demonstrated with recent publication for current research focus. These AgNPs could be used in various fields such as pharmaceuticals, cosmetics, foods and medical applications.